Plants and People in the African Past Progress in African Archaeobotany (Springer International Publishing, 2018)
Read this book to better understand the complexity and diversity of the countries of Africa. The contributions of this book investigate the adaptations and innovations that people on the African continent have developed in order to cope with their needs for food, housing and fuel in the different environments, like the Mediterranean, the desert and the tropical forest, and the changes of these environments through time. To elucidate these past interrelationships between the human agent and the environment, palaeo/archaeobotanical approaches are essential. Plants are an important part of the human diet, provide construction material for shelters and energy as fuel, and, moreover, the physiognomy of landscapes is to a large extent shaped by plants, while at same time humans have and have had an important role in shaping African environments. This book comprises the current state of the art of archaeobotanical research on the continent; archaeobotanists, botanists, anthropologists, ethnoarchaeologists, palaeoecologists, geographers and linguists bring together and discuss the evidence concerning matters such as: Plant use in foraging and agrarian societies, plant domestication, agricultural systems/history, foodways and culinary practices, human-environmental interactions, anthropic impacts and the spread of early agricultural communities. This book is the outstanding outcome of the recent meeting IWAA8 of archaeobotanists working on the African continent in Modena in 2015. The results stress the importance of integrative methods, cooperation between disciplines, and of constant exchange of data and knowledge. The meetings of the International Workgroup for African Archaeobotany were founded in 1994 with the first meeting in Mogilany, Poland. Since then workshops of African Archaeobotany have been held regularly every three years, in Leicester (1997), Frankfurt/Main (2000), Groningen (2003), London (2006), Cairo (2009), Vienna (2012) and Modena (2015).